PERANCANGAN MEDIA PEMBELAJARAN INFORMATIKA KELAS VII MENGGUNAKAN ADOBE CAPTIVATE - Haryati, Lina; Derta, Sarwo; Musril, Hari Antoni; Okra, Riri (Information Technology Education Department, 2024)
This research is focused on designing Informatics learning media for class VII Semester I at Al-Ishlah Bukittinggi Islamic Junior High School using Adobe Captivate. This research is limited to the development of valid, practical, and effective learning media, using the research and development (R&D) method and the Hannafin and Peck model. The research sample involved 4 experts for the validity test and students and teachers at Al-Ishlah Bukittinggi Islamic Junior High School for the practicality and effectiveness test. The results showed that the media developed had a high level of validity with an average value of 0.76 %, as well as practicality and effectiveness with values of 0.83 % and 0.77 % respectively. Thus, this learning media not only meets the criteria of practicality and effectiveness, but also makes a positive contribution to improving the quality of Informatics learning at the school. The implications of the results of this study indicate that technology-based learning media such as Adobe Captivate can be an effective solution to the learning problems faced, by increasing student engagement and understanding.